ECONOMIC CONSCIOUSNESS IN PHILOSOPHIC DIMENSION - Mikhail N. Mikheyev (Advanced Engineering Research, 2011)
'Economic consciousness' concept is considered from the diametrically opposed perspectives. The existent deformation of the neo-liberal model of human behaviour has increased the influence of the subjective and irrational factors on its economic activity. The necessity of forming a new development philosophy of the global system combining  the universalization of the world with its fragmentation is shown.